The Therapeutic Effects of Curcumin in Early Septic Acute Kidney Injury: An Experimental Study - Wang S; Zhao P; Zhang Y; Zhu L; Zhu J; Luo Y; Li Q (Dove Medical Press, 2021)
Shuo Wang,1,2 Ping Zhao,1,2 Ying Zhang,2 Lianhua Zhu,2 Jianing Zhu,1,2 Yukun Luo,2 Qiuyang Li2 1Medical School of Chinese PLA, Chinese PLA General Hospital, Beijing, People's Republic of China; 2Department of Ultrasound, The First Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of ChinaCorrespondence: Yukun Luo; Qiuyang LiDepartment of Ultrasound, The First Medical Center of Chinese PLA General Hospital, Fuxing Road 28#, Beijing, 100853, People's Republic of ChinaTel +86-10-5549-9056Fax +86-10-6693-9533Email lyk301@163.com; liqiuyang0925@163.comPurpose: Sepsis is the leading condition associated with acute kidney injury (AKI) in the hospital and intensive care unit (ICU), sepsis-induced AKI (S-AKI) is strongly associated with poor clinical outcomes. Curcumin possesses an ability to ameliorate renal injury from ischemia-reperfusion, but it is still unknown whether they have the ability to reduce S-AKI. The aim of this study was to investigate the protective effects of curcumin on S-AKI and to assess its therapeutic potential on renal function, inflammatory response, and microcirculatory perfusion.Methods: Male Sprague-Dawley (SD) rats underwent cecal ligation and puncture (CLP) to induce S-AKI and immediately received vehicle (CLP group) or curcumin (CLP+Cur group) after surgery. At 12 and 24h after surgery, serum indexes, inflammatory factors, cardiac output (CO), renal blood flow and microcirculatory flow were measured.Results: Serum levels of creatinine (Scr), cystatin C (CysC), IL-6 and TNF-α were significantly lower in the CLP+Cur group than those in the CLP group (P < 0.05). Treatment with curcumin improved renal microcirculation at 24h by measurement of contrast enhanced ultrasound (CEUS) quantitative parameters [peak intensity (PI); half of descending time (DT/2); area under curve (AUC); P < 0.05]. In histopathological analysis, treatment with curcumin reduced damage caused by CLP.Conclusion: Curcumin can alleviate S-AKI in rats by improving renal microcirculatory perfusion and reducing inflammatory response. Curcumin may be a potential novel therapeutic agent for the prevention or reduction of S-AKI.Keywords: curcumin, acute kidney injury, sepsis, microcirculation, inflammation, contrast enhanced ultrasound